The Effect of Process Skills Approach Using Picture Stories on Reading Comprehension and Interest in Reading in Elementary School Students - Suhrah, Suhrah; Sulfasyah, Sulfasyah; Munirah, Munirah (Institut Agama Islam Negeri Palopo, 2023)
This study aims to describe the effect of the process skills approach using picture stories on reading comprehension and reading interest of Aisyiyah Muhammadiyah 3 Elementary School Makassar fifth-grade students. This research is a quasi-experimental study with a nonequivalent control group design. The research population was all fifth-grade students at Aisyiyah Muhammadiyah 3 Makassar Elementary School, totaling 30 students. Sampling was done through the saturated sampling technique. Data was collected through tests and questionnaires and then analyzed descriptively and differentially using the Independent T-Test and the Manova Test. Based on the study's results, it can be concluded that the process skills approach using picture stories positively affects reading comprehension and reading interest in fifth-grade students of Aisyiyah Muhammadiyah 3 Makassar Elementary School.